Determination of deflection basin using pavement modelling computer programs and finite element method - Sri Atmaja, P. Rosyidi; Asmah, Hamim; Aizat, Mohd Taib; Nor Azliana Akmal, Jamaludin; Ahmed Memon, Zubair; Nur Izzi, Md. Yusoff; Mohd Rosli, Hainin (Penerbit Universiti Teknologi Malaysia, 2020)
Several methods can be used to model pavement structures, namely multi-layered elastic theory (MET), finite element method (FEM), or finite difference method (FDM). In this study, three computer programs, KENLAYER and EVERSTRESS 5.0 which are based on MET, and ANSYS, representing the FEM, are used in Falling Weight Deflectometer (FWD) test on a pavement structure to determine deflection basin. The deflection basin was developed by using the results of vertical deflection from each sensor of an FWD test. In this study, a pavement structure was modelled for three locations of FWD tests, namely CH 200, CH 1450, and CH 2300. Based on the comparative study, all computer programs show good potential in determining deflection basin, with small percentage of Root Mean Square Error (RMSE) of between 1.00% to 4.31% for all models developed by the computer programs and field measurement. In order to obtain a higher accuracy of the FEM, the models considered the dynamic loading, increasing size of model geometry, as well as the reduction of the mesh element sizes. Moreover, changing from static to dynamic loading led to the reduction of percentage in RMSE for CH 200 from 2.41% to 0.94%. Â Decreasing size of closer elements of loading region also results in lower percentages of RMSE, calculated at 4.21% to 3.63% and 1.20% to 1.18% for CH 1450 and CH 2300, respectively. FEM, therefore, is found to be the best method for determining deflection basin of FWD in comparison to other MET computer programs.